or
Don’t have an account? Sign up
or
Sign up with Google or Facebook
or
By signing up I agree to StudyBlue's
Terms of Use and Privacy Policy
Already have an account? Log in
substitution of one function into another
f(g(x))
Function denotation
add k to each y-cordinate of y=f(x) and raise the graph of f by k units
y=f(x) + k
subtract k from each y-cordinate of y=f(x) and lower the graph of f by k units
y=f(x) - k
Subtract h from each x-cordinate of y=f(x) and shift the graph of f to the left h units
y=f(x-h)
Add h to each x-cordinate of y=f(x) and shift the graph of f to the right h units
y+f(x+h)
multiply each y-cordinate of y=f(x) by -1, reflect the graph of f about the x-axis
y=-f(x)
multiply each x-cordinate of y=f(x) by -1, reflect the graph of f about the y-axis
y=f(-x)
f(x)=mx+b
a straight line that passes the vertical line test
f(x)=b
a strait horizontal line
f(x)=x^{2}
looks like a U
f(x)=x^{3}
looks kindave like and S
f(x)= 1/x
looks like a half moon facing away from the origin in the 2cd and 3rd quarters of the graph
f(x) IxI
looks like a V
the slope of two points (otherwise known as the slope of the secant line)
f(x)-f(c)
------------
x-c
"StudyBlue is great for studying. I love the study guides, flashcards, and quizzes. So extremely helpful for all of my classes!"
Alice, Arizona State University